Implementasi Nilai-Nilai Aswaja Dalam Membentuk Karakter Profil Pelajar Pancasila - Roby Permana Sapii; Ahmad Fauzi; Saiful Islam (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the implementation and internalization of Ahlussunnah Wal Jama’ah (Aswaja) values in shaping the character of the Pancasila Student Profile at SMP Zainul Hasan 2 Condong Probolinggo. This research employs a qualitative approach with a descriptive design. The research subjects include the principal, Islamic Education teachers, Aswaja local content teachers, student affairs teachers, and students. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, time triangulation, and increased persistence. The findings show that the implementation of Aswaja values is carried out in an integrated manner through religious activities, school culture habituation, and learning processes. These include congregational prayers, Yasin and tahlil recitations, the 5S culture (smile, greet, salute, politeness, courtesy), discipline habituation, deliberation, as well as discussion-based and group learning activities. Meanwhile, the internalization of Aswaja values is developed through habituation, role modeling, and continuous social interaction within the school environment. The value of tawasuth is reflected in moderate attitudes and the ability to respect different opinions, tasamuh is shown in tolerance and cooperation, tawazun appears in balancing academic and spiritual responsibilities, while i’tidal is reflected in fairness, responsibility, and deliberation in solving problems